ANTIULCER ACTIVITY OF CANAVALIA VIROSA (ROXB) W&A LEAVES IN ANIMAL MODEL: Pharmaceutical Science-Pharmacology - A.LAVANYA; KUMAR, M.PITCHIAH; J.ANBU; ANJANA, ASHWINI; S.AYYASAMY (International Journal of Life Science and Pharma Research, 2012)
Canavalia Virosa (Roxb) W&A Leaves has been widely used in Siddha system of medicine for various diseases. The powder of Kozhi Avarai Ilai Chooranam showed a significant inhibitory effect was screened at 200 mg/kg, for the in vivo antiulcer activity on chemical induced ulcer in rats. Ranitidine (60mg/kg) used as reference standard. Single dose (200 mg/kg) treatment with the siddha drug Kozhi Avarai Ilai Chooranam produced 30% antiulcer effect. The trial drug showed a significant antiulcer activity (P<0.01) and were comparable with that of standard thus validating the traditional claim of the plant.